Iconography of Beans and Related Legumes Following the Columbian Exchange - Myers, James R.; Formiga, Alice K.; Janick, Jules (Frontiers in Plant Science, 2022)
Common bean (Phaseolus vulgaris L.), maize and squash were described by explorers as early as 1492. The illustration of common bean recognized as the first in Europe is in Fuchs (1542) Di Historias Stirpium, a half-century after beans were observed in the Caribbean. Besides herbals and herbarium specimens, sources of information on the introduction of New World crops are paintings and illustrations. Two early sources of images of maize and squash are the Grandes Heures d’Anne de Bretagne and the Loggia di Amore e Psiche in the Villa Farnesina, Rome. The former was illustrated between 1507-1508, and has an image identified as common bean. The Villa Farnesina Loggia was decorated in 1515-1518, with festoons containing three instances of bean pods. Our first objective was to evaluate these images to determine whether they represented depictions of common bean earlier than the illustration by Fuchs. Neither image appears to be common bean based on a combination of botanical characters and size. Folio 194 of the Grandes Heures d’Anne de Bretagne is most likely a Vigna species in the Ceratotropis subgenus. In the Loggia, one set of pods appears to be a species in the Mimosoideae subfamily and the second and third sets of pods most closely resemble Canavalia gladiata. Neither image likely represents common bean and are probably Old World species. Secondly, illustrations of common bean from ten early herbals were analyzed for traits characteristic of the centers of domestication and races of common bean. Our objective was to characterize the diversity observed among herbals and determine whether beans from both centers of domestication were present. We potentially identified both Middle American, race Mesoamerica and Andean, race Nueva Granada types. We posit that both Middle American and Andean types were in the Caribbean at the time of the Columbian exchange, and that beans from both centers were informally introduced into Europe early on. This review of 16th century manuscripts and illustrations has provided some answers to the questions of what and when common bean reached Europe, and provides new hypotheses for researchers studying the origins, diversity and distribution of this crop.